The relationship between architecture, social, law and market in determine challenges of big data analysis for Malaysia SMEs - Min-Hooi Chuah; Ramayah Thurusamry (Cogent Business & Management, 2022)
The study aims to review the challenges of implementing big data by Malaysian small- and medium-size enterprises (SMEs)as well as to figure out the relationship between architecture, social, law and market. Currently, there is limited research and literature examining the challenges of big data analysis in Malaysia SMEs. This paper has opted for a thorough analysis of the complexities of implementing big data at SMEs in Malaysia by applying a comprehensive literature search from different databases, journals, Google scholar, IEEE and content review. This research offers practical insights into the complexities of taking Big Data in SMEs in Malaysia. It is proposed that law, architecture, social and market can be applied by Malaysian SMEs to adopt big data analytic. The authors used quantitative survey. This is done by soliciting criteria from general managers/managing directors/CEOs or data analysts from LinkedIn group. Data wereanalysed by partial least square. This research makes contribution to academics and practitioners to the emerge of predictive model to suit the challenges of big data adoption in Malaysia SMES.
Keywords: 650; big data; business analysis; Malaysia; partial least square; SMEs